The use of articles in L2 English: A phraseological perspective - Leśniewska, Justyna (Studies in Second Language Learning and Teaching, 2016)
While it is a well-known fact that speakers of article-less mother tongues, such as Polish, experience problems with articles in English, this study seeks to investigate the problem from a different perspective. Namely, it poses the question of whether the correct use of the article system of the L2 is indeed a purely grammatical task (as it is universally perceived), or whether the correct use of articles is to some extent aided by the mechanisms that underlie the formulaic character of language. The study was conducted with 90 Polish upper-intermediate and advanced users of L2 English, who completed a test on article use, which made it possible to compare patterns of article use between contexts of different collocational strength (defined in terms of the frequency of occurrence in a corpus). The statistically higher success rates for article use in high-frequency collocations (with the grammatical “rule” being the same) indicate that phraseological aspects of language use may indeed play a role in what is usually perceived as the correct application of grammatical rules.